1993
DOI: 10.1083/jcb.121.4.879
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid sequence RERMS represents the active domain of amyloid beta/A4 protein precursor that promotes fibroblast growth.

Abstract: Abstract. The growth of A-1 fibroblasts depends on exogenous amyloid ~/A4 protein precursor (APP), providing a simple bioassay to study the function of APP. Our preliminary study, testing the activity of a series of fragments derived from the secreted form of APP-695 (sAPP-695) on this bioassay, has shown that at least one of the active sites of sAPP-695 was localized within a 40-mer sequence (APP296-335, Kang sequence; Roch, J.-M., I. P. Shapiro, M. P. Sundsmo, D. A. C. Otero, L. M. Refolo, N. K. Robakis, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
95
0
4

Year Published

1994
1994
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(102 citation statements)
references
References 45 publications
3
95
0
4
Order By: Relevance
“…19,26,34,35), probably acting as a ligand for one or more unknown receptors. In contrast, Nikolaev et al reported recently that the soluble APP N terminus resulting from β-secretase cleavage (APPsβ) acts as ligand for the orphan death receptor six (DR6), leading to axon pruning and neuronal death after deprivation of other trophic factors (36).…”
mentioning
confidence: 99%
“…19,26,34,35), probably acting as a ligand for one or more unknown receptors. In contrast, Nikolaev et al reported recently that the soluble APP N terminus resulting from β-secretase cleavage (APPsβ) acts as ligand for the orphan death receptor six (DR6), leading to axon pruning and neuronal death after deprivation of other trophic factors (36).…”
mentioning
confidence: 99%
“…The large N-terminal domain of APP (residues 28 -123) contains cysteine-rich regions and a heparinbinding site and shows similarities to well known growth factors and can therefore be classified as a member of the cysteine-rich growth factor superfamily (44). The extracellular domain interacts with matrix proteins and heparan sulfate proteoglycans reflecting its role in migration, adhesion, and cell-matrix and cell-cell interactions (45)(46)(47)(48). Recently, it has been shown that APP is up-regulated in several cancer species, including pancreatic (15), colon (14), melanoma (49), and prostate cancer (17), as well as oral squamous cell carcinoma (15), and has growth-promoting features.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the interaction between APP and F-spondin could also be affected by heparin-induced E2 dimerization. The growth-promoting activities of sAPP have been attributed to an RERMS sequence motif within the E2 domain (12,34). This sequence motif is partially buried at the dimer interface.…”
Section: Discussionmentioning
confidence: 99%